Game “Three Disabled People’s Journey” Through Information Services at Junior High School 6 Palangka Raya - Esty Pan Pangestie; Mimi Suriatie; Oktamia Karuniaty Sangalang; Susi Sukarningsi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Background: Teachers are important in the activities and efficiency of information services in schools. Teachers can also act as mentors for their students. To help the education process and the quality of human resources, one of the government's policies is to raise guidance and counseling in schools by the Minister's Decree on January 15, 1975 No. 008d / 1975 and 008e / 1975, the following is emphasized again by Decree No. 84/1993 and No. 118/1996, and finally contained in the Merdeka curriculum is interest and talent. Aim: The purpose of this study is